Inlerlingual Perspectives Διαγλωσσικές Θεωρήσεις - Maria Sidiropoulou (National and Kapodistrian University of Athens/The Meta-fraseis Translation Programme, 2017)
Inlerlingual Perspectives (http://en.metafraseis.enl.uoa.gr/interlingual-perspectives-e-volume/contents-of-the-e-volume.html)/ Διαγλωσσικές Θεωρήσεις (http://metafraseis.enl.uoa.gr/metafraseologikos-h-tomos-diaglwssikes-8ewrhseis/periexomena-toy-h-tomoy.html) is a bilingual e-volume comprising occasional research articles (2010- ) focusing on the interaction of Greek with other languages through translation. Ιt invites contributions from various theoretical perspectives in translation studies (and beyond) which may shed light to the study of phenomena that are treated diffrerently cross-culturally.   The volume invites original research papers which highlight socio-cultural features of Greek in juxtaposition to other languages, as traced through translation of any type of genre: political, literary, theatrical, scientific, commercial, technical etc.   It foregrounds the potential of translators to register, in discourse, perspectives which realize dominant (or peripheral) ideological positions or narratives reverberating in a target society, whether public narratives or personal socio-political positions. The e-volume welcomes perspectives drawing on various theoretical approaches in translation studies, which may shed light on aspects of the difference of Greek vs. other languages (not necessarily the hegemonic ones). The e-volume hopes to broaden perception of interlingual variation as it is manifested through translation or interpreting. Highlighting difference in a translation context foregrounds aspects of the character of Greek vs. those of other languages, contriburing to identity awareness, aspects of translators' roles highlighting their potential to affect target culture (and the responsibility this potential assumes), while it develops competencies (professional and/or linguitic) in both languages.